Radiographic cephalometry analysis of condylar position after bimaxillary osteotomy in patients with mandibular prognathism - Miković, Nikola D.; Lazarević, Miloš M.; Tatić, Zoran; Krejović-Trivić, Sanja; Petrović, Milan; Trivić, Aleksandar (Vojnosanitetski pregled, 2017)
Background/Aim. Postoperative condylar position is a substantial concern in surgical correction of mandibular prognathism. Orthognathic surgery may change condylar position and this is considered a contributing factor for early skeletal relapse and the induction of temporomandibular disorders. The purpose of this study was to evaluate changes in condylar position, and to correlate angular skeletal measurements following bimaxillary surgery. Methods. On profile teleradiographs of 21 patients with mandibular angular and linear parametres, the changes in condylar position, were measured during preoperative orthodontic treatment and 6 months after the surgical treatment. Results. A statistically significant difference in values between the groups was found. The most distal point on the head of condyle point (DI) moved backward for 1.38 mm (p = 0.02), and the point of center of collum mandibulae point (DC) moved backward for 1.52 mm (p = 0.007). The amount of upward movement of the point DI was 1.62 mm (p = 0.04). Conclusion. In the patients with mandibular prognathism, the condyles tend to migrate upward and forward six months after bimaxillary surgery.